2013
DOI: 10.3892/ol.2013.1467
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of GSTP1, ERCC2 and TS-3′UTR are associated with the clinical outcome of mFOLFOX6 in colorectal cancer patients

Abstract: The aim of the current study was to examine whether polymorphisms in drug metabolism genes have any clinical impact on patients treated with 5-fluorouracil (FU)/oxaliplatin for metastatic colorectal cancer (MCRC). In total, 63 patients with MCRC were recruited and treated with a modified FOLFOX6 (mFOLFOX6) treatment as a first-line chemotherapy. Polymorphisms in five drug metabolism genes and two DNA-repair genes were assessed in these patients using polymerase chain reaction (PCR), a PCR restriction fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 24 publications
2
37
1
Order By: Relevance
“…An important difference is that 6bp−/6bp− genotype frequencies described in these studies are higher than those found in our cohort of patients [14,44]. A comparison of VNTR genotype frequencies in similar studies from different populations shows similarities between Mexican and Caucasian populations from Italy, Hungary and Spain (2R/2R: 16%-24%, 2R/3R: 47%-49%, 3R/3R: 29%-35%), but noticeable differences with East Asian populations (2R/2R: 4%-5%, 2R/3R: 21%-29%, 3R/3R: 67%-73%) [14,15,25,45,46]. The low frequencies of the 2R allele in the last geographical group may explain the absence of significant association between the VNTR and clinical response in these populations [47].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…An important difference is that 6bp−/6bp− genotype frequencies described in these studies are higher than those found in our cohort of patients [14,44]. A comparison of VNTR genotype frequencies in similar studies from different populations shows similarities between Mexican and Caucasian populations from Italy, Hungary and Spain (2R/2R: 16%-24%, 2R/3R: 47%-49%, 3R/3R: 29%-35%), but noticeable differences with East Asian populations (2R/2R: 4%-5%, 2R/3R: 21%-29%, 3R/3R: 67%-73%) [14,15,25,45,46]. The low frequencies of the 2R allele in the last geographical group may explain the absence of significant association between the VNTR and clinical response in these populations [47].…”
Section: Discussioncontrasting
confidence: 52%
“…However, the results are conflicting and there is no consensus on the clinical value of these variants [9][10][11]. For instance, while some studies report association between a favorable clinical response and variants at the 5′UTR and 3′UTR regulatory regions of the TYMS gene, other reports have failed to replicate such results [12][13][14][15][16]. None of these studies was performed on the Latin-American populations and studies in this group may contribute to the understanding of the biological significance of TYMS variants and their pharmacological relevance for CRC patients undergoing chemotherapy.…”
Section: Introductionmentioning
confidence: 70%
“…By contrast, one article consisted of two independent studies, and studies included in this article were treated as separate studies (MartinezBalibrea et al, 2008). As a result, a total of 2286 CRC patients were enrolled in the 17 studies included in the pool analysis (Park et al, 2001;Stoehlmacher et al, 2004;Le Morvan et al, 2007;Ruzzo et al, 2007;Martinez-Balibrea et al, 2008;Pare et al, 2008;Lai et al, 2009;Boige et al, 2010;Chen et al, 2010;Etienne-Grimaldi et al, 2010;Farina Sarasqueta et al, 2011;Lamas et al, 2011;Chen et al, 2012;Gan et al, 2012;Li et al, 2012;Kumamoto et al, 2013). The selection procedure is shown in Figure 1, and the key patient characteristics are listed by study in Table 1.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…Recently, several studies have focused on the association between ERCC1 and ERCC2 gene polymorphisms and clinical outcome of several kinds of cancers (Kumamoto et al, 2013;Nishina et al, 2013;Henríquez-Hernández et al, 2014;Li et al, 2014a;Sullivan et al, 2014;Zhou et al, 2015). However, only a few studies have reported on the role of ERCC1 and ERCC2 expression in the clinical outcome of patients with gastric cancer treated with chemotherapy (Yin et al, 2011;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%